Coffee from Cultural Perspectives: Inventorying the Local Wisdom behind Coffee Industries in Wonosobo - Pratama Rifka (EDP Sciences, 2021)
As one of the potential worldwide exports and imports, coffee’s economic and culinary values are undoubtedly outstanding. In Indonesia, the agricultural product has been increasingly prevalent and commercial. Research shows domestic coffee consumption reached 4.8 million bags of coffee beans in 2018-2019. As it continues to become more industrialized, it is also a part of nowadays’ popular culture. However, cultural perspectives to coffee production and consumption are rarely research topic priorities. Putting the perspectives as the theoretical basis, the research aims to examine, elaborate, and inventory the manifestations of local wisdom as a cultural practice behind the coffee industries in Wonosobo. The data was taken by making field observations, conducting interviews with relevant interviewees, and reviewing related literature. The result of the research reaffirms that local wisdom as a cultural practice is reflected in the process of coffee production and consumption. It takes the form of several manifestations of culture, namely symbols, rituals, and values